Neuroendocrine neoplasms of the GI tract: the role of cytotoxic chemotherapy. Issue 4 (April 2013) - Khasraw, Mustafa; Yap, Saw Yee; Ananda, Sumitra
Neuroendocrine neoplasms (NENs) comprise a heterogeneous group of neoplasms derived from peptide- and amine-secreting cells of the neuroendocrine system. NENs commonly arise in the GI tract but can arise in most organs of the body. NENs in different organs share many common pathologic features. Although the incidence of NENs is not high, the prevalence is not low because many patients may live relatively long periods without major symptoms from the disease. While many of these tumors lead an indolent clinical course, they constitute a therapeutic challenge when they progress, metastasize and become symptomatic. Treatment requires a multidisciplinary approach including cytotoxic chemotherapy. Almost all clinical trials investigating cytotoxic chemotherapy in NENs are small single-arm studies and guidelines are derived from expert opinion and from extrapolating results from small cell lung cancer studies. This article briefly reviews NENs before focusing on reviewing data on the role of cytotoxic chemotherapy studies in NENs.